Oxidative stress markers and antioxidant activity in patients admitted to Intensive Care Unit with acute myocardial infarction - Ismail, May Khalil; Samera, M. Y.; Abid, S. K. (International Journal of Health Sciences, 2018)
Objectives: The aim of the study was to compare the levels of oxidative stress biomarkers and antioxidants in acute myocardial infarction (AMI) patients with healthy individuals and to investigate the effectiveness of these parameters as risk or illness indicators. Methodology: This study was conducted on AMI patients admitted to Intensive Care Unit of Al-Salam Hospital and Ibn-Sina Hospital in Mosul, Iraq. Considering inclusion and exclusion criteria, a total of 161 patients and 156 healthy individuals in the age group of 30–80 years were selected for the study. The study groups were screened by estimating cardiac markers and electrocardiography (ECG). Results: The results indicated a significant increase in the level of serum malondialdehyde, peroxynitrite, and uric acid (P ˂ 0.001). A minor increase in the serum ceruloplasmin level was observed in patients with AMI as compared to healthy individuals. The study also observed a significant decrease in the level of glutathione, Vitamin E, and Vitamin C (P ˂ 0.001), with no significant difference in the level of Vitamin A in patients with AMI. Conclusion: The imbalance in the oxidative status and antioxidant activity in AMI patients reflects the importance of measuring the level of serum oxidative stress biomarkers and antioxidants as a diagnostic and prognostic tool for the medical management of AMI. Oxidative stress biomarkers and antioxidants might be good predictors or indicators for the risk of AMI. Oxidative stress markers contribute in the pathogenesis of AMI and excess of reactive oxygen species overwhelm the stability of the antioxidants.